(untitled) (LINGUISTIK TERAPAN, 2023)
The research aims to investigate the Impoliteness Strategies used in customers complaint on Asia™s leading airline official Instagram account. The objective of this research is to elucidate the functions of Impoliteness Strategies used by customers of Asia™s leading airline in giving online complaints on Instagram. This research employed descriptive qualitative research. The sources of data were taken from 52 customers impolite utterances posted on Asia™s leading airline official Instagram account. The result of this research shows three functions of impoliteness strategies found, Affective Impoliteness (62%), Entertaining Impoliteness (21%), Coercive Impoliteness (17%). The most dominant function used by the customers is Affective Impoliteness which earns 62%. Affective impoliteness is the targeted exhibition of strongly elevated emotion, such as rage or anger, implying that the target is responsible for the bad emotional state. Thirty-three affective impoliteness functions were identified on this airline™s official Instagram comments performed in increased emotion, such as anger, which implicates the production of negative emotions.